2019
DOI: 10.1002/ep.13312
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of green pesticide production by valorization of husks from Croton megalocarpus tree nuts

Abstract: The focus of this research is to assess the composition and the yield of wood vinegar from Croton megalocarpus husks as a function of moisture content and pyrolysis temperature as well as optimize the recovery of wood vinegar and biochar from the waste husks. C. megalocarpus is a tree found across Sub‐Saharan Africa that produces a nut twice a year that is oil dense in composition but inedible to humans. Using the process of slow pyrolysis, the wasted croton nut husks can be used to produce pyroligneous acid, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Investigate how different types of waste and agricultural by-products can be upcycled, and study the (economic) benefit of the valorization. 14 Courard, 2020;Baffes, 2010;Semiyaga et al, 2015;Montcho et al, 2016;Nzila et al, 2016;Ousseini et al, 2017;Derouiche and Ben Amor, 2019;Pfukwa et al, 2019;Anagonou et al, 2020;Ayeleru et al, 2020;Browning et al, 2020;Dibba, 2020;Munubi and Lamtane, 2021;Sekabira et al, 2021b Impact of compost, biofertilizers and other techniques on the soil, productivity, and study its challenges, (cost) benefits, and opportunities compared to conventional farming and over landfill disposal 8 Kaboré et al, 2010;Couth and Trois, 2012b;Longanza et al, 2015;Semiyaga et al, 2015;Temple and de Bon, 2020;Terfa, 2021;Obsa et al, 2022;Duponnis, n.d.…”
Section: Research Gap Frequency Authors Contributionmentioning
confidence: 99%
“…Investigate how different types of waste and agricultural by-products can be upcycled, and study the (economic) benefit of the valorization. 14 Courard, 2020;Baffes, 2010;Semiyaga et al, 2015;Montcho et al, 2016;Nzila et al, 2016;Ousseini et al, 2017;Derouiche and Ben Amor, 2019;Pfukwa et al, 2019;Anagonou et al, 2020;Ayeleru et al, 2020;Browning et al, 2020;Dibba, 2020;Munubi and Lamtane, 2021;Sekabira et al, 2021b Impact of compost, biofertilizers and other techniques on the soil, productivity, and study its challenges, (cost) benefits, and opportunities compared to conventional farming and over landfill disposal 8 Kaboré et al, 2010;Couth and Trois, 2012b;Longanza et al, 2015;Semiyaga et al, 2015;Temple and de Bon, 2020;Terfa, 2021;Obsa et al, 2022;Duponnis, n.d.…”
Section: Research Gap Frequency Authors Contributionmentioning
confidence: 99%
“…Pyrolysis process consists of primary and secondary stages which involves devolatisation of the main components and thermal cracking of heavy compounds in to gases such as carbon monoxide, carbon dioxide, methane and hydrogen (Aguirre et al, 2020). The process results to formation of various products and has minimal emissions of greenhouse gases to the atmosphere (Browning et al, 2020). Biooil which is the dark brown liquid obtained after pyrolysis process has two layers where the top layer is in aqueous phase with low viscosity and large amount of water soluble compounds known as pyroligneous acid and the bottom layer consisting of organic material with high viscosity referred to as tar (Qin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In producing pyroligneous acid, the pyrolysis smoke is condensed and it can be generated from any type of organic waste that is readily available. Browning et al (2020) reported that pyroligneous acid is environmentally friendly, economically viable, socially acceptable and used in many parts of the world especially in developing countries. The product has more than 200 natural compounds with its principal components being acetic acid and phenols which can be used as soil disinfectant to increase crop yield while utilizing less water (Than and Suluksna, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Pyrolysis process consists of primary and secondary stages which involves devolatisation of the main components and thermal cracking of heavy compounds in to gases such as carbon monoxide, carbon dioxide, methane and hydrogen [1]. The process results to formation of various products and has minimal emissions of greenhouse gases to the atmosphere [4]. Bio-oil which is the dark brown liquid obtained after pyrolysis process has two layers where the top layer is in aqueous phase with low viscosity and large amount of water soluble compounds known as pyroligneous acid and the bottom layer consisting of organic material with high viscosity referred to as tar [13].…”
Section: Introductionmentioning
confidence: 99%
“…In producing pyroligneous acid, the pyrolysis smoke is condensed and it can be generated from any type of organic waste that is readily available. Browning et al [4] reported that pyroligneous acid is environmental friendly, economically viable, socially acceptable and used in many parts of the world especially in developing countries. The product has more than 200 natural compounds with its principal components being acetic acid and phenols which can be used as soil disinfectant to increase crop yield while utilizing less water [15].…”
Section: Introductionmentioning
confidence: 99%